How much aid is good for Africa - a big push as a way out of the "poverty trap"? - Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
For sub-Saharan Africa (SSA) the year 2005 offers a number of important opportunities for political action (G8 summit; debate on the report on the Commission for Africa – CFA; review of the progress made on achieving the Millennium Development Goals – MDGs). On the one hand, this is a chance that should not be missed; on the other, it would be important to ensure that this process is not narrowed down, resulting in a focus on overly simplistic declarations and options for action. Against the background defined by successes in development that have, on the whole, either failed to materialize or proven insufficient, and that are reflected in the indicators on the (non-)achievement of the MDGs, there is an intensive debate underway on the African continent, one that casts light on some of the different dimensions of the debate. The first question involved here concerns approaches to explaining existing development deficits. What we increasingly find here is a polirization between approaches that see the central governance problems on the one side and in “poverty traps” and classic structural deficits (high transportation costs, etc.) on the other. And there is no reason to believe that income growth leads automatically to better governance performance. In the second place, the massive increase in the official development assistance (ODA) provided in recent years – which has included just under US 24 billion (2003) for sub-Saharan Africa – has come to play a prominent role in the conclusions reached by some important analyses. Arguments in favour of increasing ODA are countered with arguments that point to possible inappropriate incentives (a declining need to mobilize national resources, etc), negative collateral impacts, and lack of the technical-administrative absorption capacities required. In the third place, the debate is concerned with some fundemental questions involved in a reform of ODA designed to improve the quality and effectiveness of development assistance. Both the international consensus reached in the Paris Declaration on Aid Effectiveness (February 2005) and other, more extensive proposals (e.g. regarding program-based approaches, the need to make more intensive use of partner structures) play an important role in this connection. On the whole, it is important to prevent these controversial debates from deteriorating into an unfruitful ,,doctrinal dispute.“ What is needed instead is efforts to specify, primarily at country level, the central causes for given problems (Is it certain country policies that may develop key impacts? Or is the core problem rooted in funding bottlenecks?). In sum, there is, on the one hand, no getting away from the need for African partners to devote more efforts to coming to terms with central governance deficits (cleptocratic systems, violent conflict, deficient rule of law, etc.); but on the other hand the donors must be expected to implement their commitments to increase their ODA, step up their efforts to raise the effectiveness of ODA, and to create incentives designed to promote good governance and avoid bad governance.
Keywords: 330